2009
DOI: 10.5465/amj.2009.37308149
|View full text |Cite
|
Sign up to set email alerts
|

Searching for The Optimal Level of Employee Turnover: A Study of a Large U.K. Retail Organization

Abstract: We study the relationship between sales assistant turnover and labor productivity in 325 stores of a large U.K. clothing retailer tracked over 1995-99. We find that the turnover-productivity relationship is contingent on type of work system. For a large group of part-timers, managed under a "secondary" work system, the relationship clearly has an inverted U-shape, but for the smaller group of full-timers, managed under a "commitment" system, the relationship is the conventional negative one. Implications for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
191
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(200 citation statements)
references
References 43 publications
7
191
0
2
Order By: Relevance
“…Particularly, substantial attention has been paid to organizational turnover intention in an effort to understand the mechanisms behind voluntary turnover behavior, which is directed at reducing turnover and its potential costs [44,45]. Indeed, Siebert and Zubanov [45] emphasize that turnover intention can result in negative consequences, such as difficulties in recruitment, training expenses, declining employee morale, and customer dissatisfaction. Some argue that recruiting and training a replacement employee can cost up to 50% of the worker's annual salary [46].…”
Section: Turnover Intention and Perceived Organizational Sustainabilimentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, substantial attention has been paid to organizational turnover intention in an effort to understand the mechanisms behind voluntary turnover behavior, which is directed at reducing turnover and its potential costs [44,45]. Indeed, Siebert and Zubanov [45] emphasize that turnover intention can result in negative consequences, such as difficulties in recruitment, training expenses, declining employee morale, and customer dissatisfaction. Some argue that recruiting and training a replacement employee can cost up to 50% of the worker's annual salary [46].…”
Section: Turnover Intention and Perceived Organizational Sustainabilimentioning
confidence: 99%
“…Conversely, according to Park and Shaw [16], a high turnover rate makes it difficult for companies to build effective teams and therefore results in low social performance. Siebert and Zubanov [45] suggest that social capital is created when the relationship among people changes in ways that faciliate instrumental action. This could imply that increases in turnover cause disruptions to operational and collective functions [51].…”
Section: Turnover Intention and Perceived Organizational Sustainabilimentioning
confidence: 99%
“…Teacher turnover is not necessarily detrimental. In general, theory and research from the fields of organizational theory, economics and sociology have long held that some degree of employee turnover is normal and inevitable, and can be efficacious for individuals, for organizations, and for the economic system as a whole (e.g., Price, 1977Price, , 1989Jovanovic, 1979aJovanovic, , 1979bMobley, 1982;Abelson & Baysinger, 1984;Hom & Griffeth, 1995;Siebert & normal and common, perhaps increasingly so, and some hold that high levels of employee turnover are a sign of economic opportunity and a dynamic, well-functioning economy (e.g., Kimmitt, 2007). Moreover, researchers have concluded that effective organizations usually promote some degree of employee turnover and benefit from it by the departure of low-caliber performers and the recruitment of "new blood" to facilitate innovation.…”
Section: Trends In Minority Teacher Turnovermentioning
confidence: 99%
“…Topical interest further formalized via several influential accounts of collective turnover's causes and consequences (March & Simon, 1958;Mobley, 1982;Price, 1977;Staw, 1980). More recently, this attention has intensified in terms of empirical studies (e.g., Batt & Colvin, 2011;Shaw, Dineen, Fang, & Vellella, 2009;Siebert & Zubanov, 2009;Trevor & Nyberg, 2008), theoretical contributions (Dess & Shaw, 2001), and narrative reviews (Hausknecht & Trevor, 2011;Shaw, 2011). Indeed, over 100 studies have been published on the topic-nearly two thirds in the last decade alone-mostly in leading journals in management and related fields (Hausknecht & Trevor, 2011).…”
mentioning
confidence: 99%